A case report: Pathological complete response to neoadjuvant lorlatinib for Epithelioid inflammatory myofibroblastic sarcoma with EML4-ALK rearrangement - Zheng, Yang; Zhao, Fanfei; Ren, Yaqian; Xue, Yaran; Yan, Bing; Huang, Chun (Frontiers in Pharmacology, 2024)
Inflammatory myofibroblastic tumor (IMT) is a rare tumor originating from mesenchymal tissue. Epithelioid inflammatory myofibroblastic sarcoma (EIMS) represents a rare and particularly aggressive variant, associated with a worse prognosis. Almost all EIMS cases exhibits activating anaplastic lymphoma kinase (ALK) gene rearrangements, which suggests that EIMS patients may potentially benefit from treatment with ALK tyrosine kinase inhibitors (TKIs). We presented a case involving a 34-year-old woman who was diagnosed with mediastinal EIMS and had a rare EML4-ALK fusion. Following 15 months of neoadjuvant lorlatinib treatment, the patient underwent a complete surgical resection, resulting in a pathological complete response. Given the heightened risk of postoperative recurrence associated with EIMS, the patient's treatment plan included ongoing adjuvant therapy with lorlatinib. As of the present moment, the patient has achieved an overall survival of over two years with no observed tumor recurrence. Consequently, the case offers valuable clinical evidence supporting the potential benefits of neoadjuvant lorlatinib treatment for ALK-positive locally mediastinal EIMS patients, with a demonstrated tolerable safety profile.